Retinal Pigment Epithelial Cells Express a Functional Receptor for Glucagon-Like Peptide-1 (GLP-1) - Puddu, Alessandra; Sanguineti, Roberta; Montecucco, Fabrizio; Viviani, Giorgio L. (Mediators of Inflammation, 2013)
Glucagon-like peptide-1 (GLP-1) is a gut-derived incretin hormone that has been shown to improve glucose homeostasis in type 2 diabetes. The biological effects of GLP-1 are mediated by its specific receptor GLP-1R that is expressed in a wide range of tissues, where it is responsible of the extra-pancreatic effects of GLP-1. Since the retinal pigment epithelium (RPE), that forms the outer retinal barrier, has a key role in protecting from diabetic retinopathy (DR), we investigated the potential expression and function of GLP-1R in a RPE cell line. ARPE-19 cells were cultured in DMEM/F12 supplemented with 10% FBS. The expression of GLP-1R was evaluated at both mRNA and protein levels. Then, the activation postreceptor intracellular signal transduction pathways (extracellular signal-regulated kinases 1 and 2 [ERK1/2] and protein kinase B [PKB]) were assessed by western blot in normal cells or silenced for GLP-1R in the presence or absence of 10 nmol/L GLP-1. The potential connections between intracellular signalling pathways triggered by GLP-1 stimulation were performed before incubating cells with kinase pharmacological inhibitors of mitogen-activated protein kinase (MEK)1/2, phosphatydilinositol-3kinase (PI3K), or epidermal growth factor receptor (EGFR). The results showed that GLP1R is expressed at both mRNA and protein level in ARPE-19 cells. Stimulation with GLP-1 strongly activated PKB and ERK1/2 phosphorylation till 40 min of exposure. GLP-1-mediated activation of both kinases was dependent on the upstream activation of PI3K and EGFR. Finally, treatment with GLP-1 did not affect the spontaneous release of VEGF-A from ARPE-19 cells. In conclusion, this paper showed that the presence of functional GLP-1R is expressed in RPE cells. These data might represent the rationale to further investigate the potential direct beneficial effects of GLP-1 treatment against DR.